Peran Kepala Sekolah dalam Meningkatkan Kinerja Guru di Madrasah Ibtidaiyah - Zachary, Muhammad Ezar; Fathoni, Achmad (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The school principal plays a crucial role in enhancing the quality and performance of teachers, as the quality of teachers significantly influences student development. High-quality teachers can create high-quality education, and the best graduates are usually produced by quality teachers in the institution. This study aims to describe the principal's role as an educator in improving the quality and performance of teachers at Madrasah Ibtidaiyah Muhammadiyah Gonilan, Kartasura, Sukoharjo, using a descriptive qualitative approach. The subjects of this research are the principal and teachers of grades 1, 2, and 4. Data collection methods include observation, interviews, and documentation. The results show that the principal plays a role in improving the quality and performance of teachers through guidance, instructing teachers to attend training, and conducting teacher performance evaluations. As a manager, the principal organizes the school's agenda to be structured and in accordance with procedures for the upcoming year and understands the conditions and capabilities of the teachers. As an administrator, the principal checks administration, correspondence from the education department, teacher activity permits, and learning tools. The recommendation of this research is for the principal to further enhance teacher performance through motivation and supervision. Although the principal has performed his role well, it would be even better if there were new innovations in programs to improve teacher performance, particularly in the role as an educator.